Amplified spontaneous emission from a microtube cavity with whispering gallery modes - DONEGAN, JOHN; PEROVA, TANIA; RAKOVICH, YURY; GOUNKO, IOURI (My University, 2007)
We present a detailed study of the photonic modes in microtube cavity of ~ 7-8 ?m outer diameter that can act as micron-scale optical cylindrical resonator. We demonstrate a new route to the fabrication of individual microtubes with the maximum length of 200 ?m, using a vacuum assisted wetting and filtration through a microchannel glass matrix. The microtubes were studied using micro-photoluminescence spectroscopy and luminescence lifetime imaging confocal microscopy. In the emission spectra of the microresonators we find periodic very narrow peaks corresponding to the whispering gallery modes of two orthogonal polarizations with quality factors upto 3200 at room temperature. In order to identify the peaks in the observed mode structure, we have adopted the boundary-value solution to the problem of scattering of electromagnetic waves by a dielectric micro-cylinder. A strong enhancement in photoluminescence decay rates at high excitation power suggest the occurrence of amplified spontaneous emission from a single microtube. The evanescent field in these photonic structures extends a couple of micrometers into the surroundings providing the possibility for efficient coupling to an external photonic device.
Proceedings of SPIE - The International Society for Optical Engineering
Photonic Materials, Devices, and Applications II
PUBLISHED
Ali Serpengüzel, Gonçal Badenes, Giancarlo C. Righini, Editors
Keywords: Physics